“An Extensive Collection of Useful and Entertaining Books”: The Quebec Library and the Transatlantic Enlightenment in Canada - Eamon, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
At the height of the American Revolution in 1779, the Quebec Library was created by Governor Sir Frederick Haldimand. For Haldimand, the library had a well-defined purpose: to educate the public, diffuse useful knowledge, and bring together the French and English peoples of the colony. Over the years, the memory of this institution has faded and the library has tended to be framed as an historical curiosity, seemingly divorced from the era in which it was created. This paper revisits the founding and first decades of this overlooked institution. It argues that its founder, trustees, and supporters were not immune to the spirit of Enlightenment that was exhibited elsewhere in the British Atlantic World. When seen as part of the larger social and intellectual currents of the eighteenth century, the institution becomes less of an historical enigma and new light is shed on the intellectual culture of eighteenth-century Canada.